2020
DOI: 10.1007/s00705-020-04860-8
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline and viruses: a possible treatment for COVID-19?

Abstract: Tetracyclines have been used to treat many bacterial infections. The use of these antibiotics for the treatment of viral diseases dates to the 1960s to 1970s. Over the decades, the effect of tetracyclines on the pathogenesis of viral infections has been demonstrated both clinically and experimentally. Tetracyclines can act on viral infections either through their antibacterial properties or through direct antiviral action. This review focuses on clinical and experimental data that support the use of tetracycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 72 publications
0
33
0
1
Order By: Relevance
“…Since it is difficult to predict the progression of SARS-CoV-2 infection, it is reasonable to adopt measures to inhibit the virus to prevent severe illness. Antiviral treatment at the onset of SARS-CoV-2 infection may be important for preventing severe disease in elderly patients, patients at high risk, and in the general population to allow a more effective response by the immune system [105].…”
Section: Discussionmentioning
confidence: 99%
“…Since it is difficult to predict the progression of SARS-CoV-2 infection, it is reasonable to adopt measures to inhibit the virus to prevent severe illness. Antiviral treatment at the onset of SARS-CoV-2 infection may be important for preventing severe disease in elderly patients, patients at high risk, and in the general population to allow a more effective response by the immune system [105].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that doxycycline may have beneficial effects for people affected by the newly emerged coronavirus disease 2019 (COVID19) due to its antiviral and anti-inflammatory properties [ 52 , 53 ]. The latter seem particularly relevant, as dysregulation of the innate immune responses and the cytokine storm have been associated with severe COVID19 cases [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, based on the reporting and clinical experience, the early therapeutics that we advocate for such as HCQ, ivermectin, and doxycycline etc. 12,17, 18, 38, 39 ) may potentially function by working to inhibit viral replication while also dampening the host innate immune response thereby reducing oxidative stress, matrix-metalloproteinase-mediated inflammation/tissue damage, as well as the production of a wider array of inflammatory cytokines. In the meantime then and given the dearth of such randomized evidence that would provide clarification, and given the present emergency crisis, the observational non-randomized data we reviewed which we judged as acceptable to informing this report (and in line with expert arguments for observational study evidence use especially when RCT evidence is not available or is in many cases, of poor methodological quality), 43 suggest a treatment mandate is present and should replace therapeutic nihilism for nursing home residents with acute COVID-19.…”
Section: Discussionmentioning
confidence: 99%